The Functional Competence State of Patients with Rheumatic Arthritis and Different Variants of Polymorphic Site of 5-HTR2A T102C Gene or A-1438-G Depending on Sex - L. O. Protsiuk (Zaporožskij Medicinskij Žurnal)
The state of functional competence in 100 patients with RA and different variants of polymorphic sites of serotonin receptor 5-HT2A T102C or A-1438-G gene was studied using the Health Assessment Questionnaire (HAQ). Polymorphic sites of T102C or A-1438-G gene were amplified with polymerase chain reaction. Anxiety level was assessed by Spielberger State-Trait Anxiety Scale (STAI). Depressive status and depression severity were evaluated by Hamilton Depression Rating Scale (HDRS).